2010
DOI: 10.1167/iovs.09-4730
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Patterns of Histone Lysine Methylation in the Developing Retina

Abstract: HKM is a dynamic and spatiotemporally regulated process in the developing retina. Epigenetic regulation of gene transcription by Ezh2- and G9a-mediated HKM plays crucial roles in retinal neuron survival and may represent novel epigenetic targets to enhance viability in retinal neurodegenerative diseases such as glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 65 publications
4
49
0
1
Order By: Relevance
“…1D). Ezh2 is known to be highly expressed in the retina in the INBL at E16 but is undetectable in adult retina (19). RT-qPCR showed that the level of Ezh2 decreased after birth, and when retinal development was complete at about 2 wk after birth, Ezh2 expression was negligible (Fig.…”
Section: Significancementioning
confidence: 94%
“…1D). Ezh2 is known to be highly expressed in the retina in the INBL at E16 but is undetectable in adult retina (19). RT-qPCR showed that the level of Ezh2 decreased after birth, and when retinal development was complete at about 2 wk after birth, Ezh2 expression was negligible (Fig.…”
Section: Significancementioning
confidence: 94%
“…29 However, H3K9me2 has been implicated in the terminal commitment of blood, cardiac, retinal, neural, muscle and germline lineages. 23,25,29,[40][41][42][43] For example, H3K9me2 plays a dynamic role in retinal progenitor cells 44 and loss of Ehmt2 mediated epigenetic repression leads to profound defects in the early retina. Zebrafish ehmt2 morphants show severe decreases in crx, neuroD and irbp gene expression; markers of retinal cell differentiation.…”
Section: Canonical Roles Of Ehmt1/2 Complexmentioning
confidence: 99%
“…In order to identify possible patterns of HKM during retinal development, a recent study used a variety of methylated lysine-specific antibodies to probe retinal sections during different periods of murine retinogenesis [16]. An antibody against tri-methylated K4 of H3 (H3K4me3), an HKM mark associated with active gene transcription and euchromatin, was detected throughout the inner retina and outer retina during the proliferative phases of retinogenesis.…”
Section: Histone Methylation In Retinal Ganglion Cellsmentioning
confidence: 99%
“…Another report demonstrated the regulation of atonal homolog 5 (Ath5), a member of the basic helix-loop-helix [16,17] Present in all layers in adult murine retina [16], associated with transcription of ATH5 in newly born RGCs in chick retina [18].…”
Section: Histone Methylation In Retinal Ganglion Cellsmentioning
confidence: 99%
See 1 more Smart Citation